THE EFFECT OFLANGUAGE DIFFERENCES AND TYPES OFILLUSTRATION MUSIC IN MEDIA AUDIO FISHERY DISCUSSION ON IMPROVEMENT OF KNOWLEDGE OF FISH AQUACULTURER IN KOTO TINGGI VILLAGE KOTO BESAR DISTRICT DHAMASRAYA REGENCY WEST SUMATERA PROVINCE - AdhilFajri AdhilFajri; Firman Nugroho; Ridar Hendri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was conducted in June-July 2017 in Koto Tinggivillage. The purpose of this study was to analyze the influence of different types of languages and music illustrations to the level of knowledge of Aquaculturer in audio extension media in Koto Tinggivillage Koto Besar District Dhamasraya Regency West Sumatra Province. The method used in this research is the experimental method.The extension was done once and was attended by 20 audients. The pre test and post test marks were then compared. The results showed that: a) Fisheries extension in Dhamasraya District amounted to 3 people, so far the extension activities always use conventional methods such as: lecture method and media leaflet, while audio media has never been used; b) based on the results of statistical tests and observations, the differences in the type of language and music illustrations contained in audio counseling media conducted in Nagari Koto Tinggi can affect the knowledge level of fish farmers in Nagari Koto Tinggi; c) the percentage difference between pre test and post test results in audio with Minang language and music of Minang 33,3%, bigger than pre test result and post test in audio with Indonesian language and Pop music (Indonesia) which is 25%. The conclusion of this research is the difference of language and type of music in media of audio extension can influence the knowledge level of fish farmer. Audio extension media using Minang language and Minang music illustration is more effective in increasing knowledge of fish farmers in Nagari Koto TinggiKeywords: Extension Methods, Fisheries Extension, Audio-visual Media.